Respuesta :

The average rate of change from x =-2 to 1 is -7 and the equation of the secant line is y = -7x + 11

How to determine the average rate of change?

The function is given as:

g(x) = 7x^2 - 3

Calculate g(-2) and g(1)

g(-2) = 7(-2)^2 - 3 = 25

g(1) = 7(1)^2 - 3 = 4

The average rate is then calculated as:

[tex]m = \frac{g(-2) - g(1)}{-2 - 1}[/tex]

This gives

[tex]m = \frac{25 - 4}{-3}[/tex]

Evaluate

m = -7

Hence, the average rate of change from x =-2 to 1 is -7

The equation of the secant line

This is calculated using:

y = m(x -x1) + y1

So, we have:

y = -7(x + 2) + 25

Evaluate

y = -7x + 11

Hence, the equation of the secant line is y = -7x + 11

Read more about average rates at:

https://brainly.com/question/8728504

#SPJ1